The effect of job satisfaction, transformational leadership and interpersonal communication on organizational citizenship behavior - Herfina Herfina; Widodo Sunaryo; Martinus Tukiran; Dian Wulandari; Herlinda Herlinda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The purpose of this study was to determine the direct effect of Job Satisfaction on Organizational Citizenship Behavior (OCB) and the indirect effect of Job Satisfaction on OCB through the mediation of Transformational Leadership and Interpersonal Communication. Job Satisfaction as the independent variable, the variables of Transformational Leadership and Job Satisfaction as the mediating variable, and OCB as the dependent variable. The research sample involved was from 266 teachers who were selected by proportional random sampling from 20 junior high schools in the city of Bogor, West Java. This research uses Path analysis technique with PLS-SEM Program. This research concludes that: (1) Job Satisfaction has a significant positive direct effect on OCB ( = 0.358 p < 0.01), (2) Job Satisfaction has a significant positive effect on Transformational Leadership ( = 0.755 p < 0.01), (3) Job Satisfaction has a significant positive effect on Interpersonal Communication ( = 0.941 p < 0.01), (4) Transformational Leadership has a significant positive effect on OCB ( = 0.185 p < 0.05), (5) Interpersonal Communication has a significant positive effect on OCB ( = 0.337 p < 0.01), (6) Job satisfaction has a significant positive effect on OCB through the mediation of Transformational Leadership ( = 0.140 p < 0.05), (7) Job Satisfaction has a significant positive effect on OCB through the mediation of Interpersonal Communication ( = 0.317 p < 0.01). Based on the conclusions of the research results above, the strengthening of OCB can be carried out directly through increasing job satisfaction and can be done indirectly through increasing job satisfaction through the mediation of interpersonal communication.